Artificial neural networks for modeling wood volume and aboveground biomass of tall Cerrado using satellite data - Miguel, Eder Pereira; Rezende, Alba Valéria; Leal, Fabrício Assis; Matricardi, Eraldo Aparecido Trondoli; Vale, Ailton Teixeira do; Pereira, Reginaldo Sergio (Pesquisa Agropecuaria Brasileira, 2015)
The objective of this work was to evaluate the effectiveness of regression models and artificial neural networks (ANNs) in predicting wood volume and aboveground biomass of arboreal vegetation in area of tall Cerrado (a forest, savanna‑like vegetation). Wood volume and biomass were estimated with allometric equations developed for the studied area. The vegetation indices, as predictor variables, were estimated from LISS‑III sensor imagery, and the basal area was determined from field measurements. Equation precision was verified by the correlation between estimated and observed values (r), standard error of estimate (Syx), and by the residual plot. The regression equations for total wood volume and bole volume (0.96 and 0.97 for r, and 11.92 and 9.72% for Syx, respectively), as well as for aboveground biomass (0.91 and 0.92 for r, and 22.73 and 16.80% for Syx, respectively) showed good adjustments. The neural networks also showed good adjustments for both wood volume (0.99 and 0,99 for r, and 4.93 and 4.83% for Syx) and biomass (0.97 and 0.98 for r, and 8.92 and 7.96% for Syx, respectively). Basal area and vegetation indices were effective in estimating wood volume and biomass for the tall cerrado vegetation. Measured wood volume and aboveground biomass did not differ statistically from the predicted values by both the regression models and neural networks (χ²ns); however, the ANNs are more accurate.